The Effect of Campus Facility Quality, Facility Accessibility, Facility Maintenance, and Service Support of STIE Ciputra Makassar on Student Satisfaction Using the SERVQUAL and SOR (Stimulus-Organism-Response) Approaches - Christian Philetas Liem; Vivian Wong; Andisva Fridy Fathiar; Monalisa (Accounting Profession Journal (APAJI), 2025)
This study aims to examine the impact of the quality of facilities at STIE Ciputra Makassar on student satisfaction. This research is motivated by the important role of higher education facilities in the management of higher education institutions and the significant relationship between the quality of facilities and student satisfaction as demonstrated in previous studies. This research uses a quantitative method with a survey design. Data was collected from STIE Ciputra Makassar students through questionnaires and analyzed using descriptive statistics. The results of this study are expected to contribute to the development of knowledge and understanding of the impact of campus facility quality on student satisfaction, as well as assist STIE Ciputra Makassar in improving the quality of its campus facilities, thereby enhancing student satisfaction.